The Cu-Li-Mg system for hydrogen storage - Helena Braga (2020)
- Plenary talk - A family of hydrides, including the high capacity MgH 2 and LiH, is reported. The disadvantages these hydrides normally display (high absorption/desorption temperatures and poor kinetics) are mitigated by Cu-hydride catalysis. The CuLi 0.08 Mg 1.42 H 4 and CuLi 0.08 Mg 1.92 H 5 hydrides are characterized. The CuLi 0.08 Mg 1.42 H 4 structure in nanotubes is able to hold molecular H 2 , increasing the gravimetric and volumetric capacity of this compound. The catalytic effect these compounds show on hydride formation and decomposition of CuMg 2 and Cu 2 Mg/MgH 2 , Li and LiH, Mg and MgH 2 is analyzed. The Gibbs energy, decomposition temperature, and gravimetric capacity of the reactions occurring within the Cu-Li-Mg-H system are presented. First principles and phonon calculations are compared with experiments, including neutron spectroscopy. It is demonstrated that the most advantageous sample contains CuLi 0.08 Mg 1.92 and (Li)∼Li 2 Mg 3 ; it desorbs/absorbs hydrogen according to the reaction, 2CuLi 0.08 Mg 1.42 H 4 +2Li+4MgH 2 ↔2CuLi 0.08 Mg 1.92 +Li 2 Mg 3 +8H 2 at 114°C (5.0 wt%) - 1 atm, falling within the proton exchange membrane fuel cell applications window.